The backsmart fitness plan a total-body workout to strengthen and heal your back - Weiss, Adam (McGraw Hill, 2005)
This fitness plan is a proven program designed to strengthen the back and prevent injuries. In this step-by-step program, Dr. Adam Weiss presents an organized routine of exercises to improve physical strength, flexibility, balance, muscular endurance, and appearance, all without causing stress or injury to the joints and ligaments